METHODLOGY FOR DEVELOPING CHILDREN’S GRAMMATICALLY CORRECT SPEECH IN PRESCHOOL EDUCATIONAL INSTITUTIONS - Abduraimova Sevara Sodiq qizi; Abdukaimova Sitora Alisher qizi (TADQIQOTLAR, 2025)
Abstract: This research paper examines the methodology for developing grammatically correct speech among preschool children. It explores linguistic, psychological, and pedagogical foundations of grammar development, identifies key factors influencing children’s speech, and analyzes effective methods and approaches used in preschool educational institutions. The study emphasizes the importance of communicative, play-based, and integrated learning environments. Practical recommendations, classroom activities, and teacher strategies are provided to support the development of children’s grammatically correct speech. The paper concludes with an overview of challenges and solutions in early grammar instruction.